Tingkah Laku Makan Domba Lokal pada Sistem Pemeliharaan Berbeda - I. Munandar; M. Yamin; D. A. Astuti; S. Rahayu (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2022)
Sheep is a livestock commodity this is used to meet national meat needs. This response takes a look at goals to look at social conduct and consume nearby sheep, which can be maintained in one of a kind renovation structures and supply one of a kind styles of concentrates. Looking at the 20 sheep used, their initial weight was 16.51 kg. Experiments were conducted throughout random layouts. The first part is device renovation and the second one part is the form of feed listen. The parameters discovered beating, mastication, remastication, regurgitation, length of eating. Data become analyzed with the aid of using evaluation of variance (ANOVA). The consequences of the take a look at confirmed that the form of listen and renovation device affected meals conduct (beating, mastication of remastication and regurgitation, length of eating).